The Impact of Chain of Command in an Organization - Malgorzata MATYJA; Magdalena RAJCHELT-ZUBLEWICZ (Communications of International Proceedings, 2020)
Research motivation. This paper is in line with the assumption that the organizational structure of the future will be an adapting hierarchy, and its perfection will be expressed in adapting to nature and human needs. One of them is a chain of command, frequently replaced by the term “scalar chain” or “line of authority”. The aim of the study is the theoretical and empirical examination of the influence of the chain of command on different fields in organizations. Research design/methodology. This paper uses the methodology of survey research on a representative example of one country (Poland). The data was obtained from a survey on 252 employees of various types of organizations. In the empirical data analysis the Mann–Whitney U test was used. Main findings and implications. The authors indicated fifteen fields of an organization which may be affected by the chain of command: attitude to innovation, initiatives, staff morality, decision-taking process, decision-taking process, managers' responses in case of their rating, or of their circumvention, overall performance, employees' performance, employees' wages, employees' commitment, conflicts and stalemates, supervisors' control, superior-subordinate relationship and choice of competitive strategy. However, they were able to empirically confirm the impact on only three of them: initiatives, decision-taking process and employees’ wages. Nevertheless, the authors do not advise to resign from the chain of command in organizations. All its advantages stands up for it. They suggest to pay more attention to these three fields in the face of adherence to the idea of the chain of command.
Keywords: Chain of command; hierarchy; authority; organization.